2016
DOI: 10.1371/journal.pgen.1005935
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking Endoglin in Macrophages Show an Impaired Immune Response

Abstract: Endoglin is an auxiliary receptor for members of the TGF-β superfamily and plays an important role in the homeostasis of the vessel wall. Mutations in endoglin gene (ENG) or in the closely related TGF-β receptor type I ACVRL1/ALK1 are responsible for a rare dominant vascular dysplasia, the Hereditary Hemorrhagic Telangiectasia (HHT), or Rendu-Osler-Weber syndrome. Endoglin is also expressed in human macrophages, but its role in macrophage function remains unknown. In this work, we show that endoglin expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 52 publications
2
43
0
1
Order By: Relevance
“…This phenotype was rescued by the injection of mononuclear cells from healthy human donors but not by mononuclear cells from HHT1 patients. This result is in agreement with the reduction in monocyte function (including oxidative burst and phagocytosis) in HHT patients [242] and in mouse monocytes lacking endoglin [243]. Moreover, a different role for endoglin isoforms in the regulation of monocyte-macrophage functions has been proposed because L-endoglin overexpression promotes a pro-inflammatory M1-like macrophage phenotype, whereas S-endoglin favors the expression of anti-inflammatory M2 macrophage markers [96].…”
Section: Endoglin Regulation Of Mural and Mononuclear Cell Recruitmentsupporting
confidence: 85%
“…This phenotype was rescued by the injection of mononuclear cells from healthy human donors but not by mononuclear cells from HHT1 patients. This result is in agreement with the reduction in monocyte function (including oxidative burst and phagocytosis) in HHT patients [242] and in mouse monocytes lacking endoglin [243]. Moreover, a different role for endoglin isoforms in the regulation of monocyte-macrophage functions has been proposed because L-endoglin overexpression promotes a pro-inflammatory M1-like macrophage phenotype, whereas S-endoglin favors the expression of anti-inflammatory M2 macrophage markers [96].…”
Section: Endoglin Regulation Of Mural and Mononuclear Cell Recruitmentsupporting
confidence: 85%
“…ACVRL1 is a transmembrane protein of the transforming growth factor beta superfamily, which mediates the bone morphogenetic protein (BMP) 9-and BMP10-induced signaling that orchestrates the development of blood vessels [73]. This relates to the control of monocyte to macrophage differentiation [74]. SRGN is a secreted proteoglycan of endothelial cells, monocytes, mast cells and lymphocytes [75].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a mouse model where ENG, one of genes involved in HHT, was conditionally deleted in myeloid lineage, it was found that 30% of conditional knockout mice developed spontaneous soft tissue abscesses. 18 Additional studies revealed impaired macrophage functions in these conditional knockout mice, including transmigration and phagocytosis. It is unclear how the HHT-associated macrophage defects might affect alloimmunization.…”
Section: Discussionmentioning
confidence: 96%
“…Cirulli and coworkers examined 20 patients with HHT and found that their neutrophils and monocytes were defective in oxidative burst and phagocytosis. Furthermore, in a mouse model where ENG, one of genes involved in HHT, was conditionally deleted in myeloid lineage, it was found that 30% of conditional knockout mice developed spontaneous soft tissue abscesses . Additional studies revealed impaired macrophage functions in these conditional knockout mice, including transmigration and phagocytosis.…”
Section: Discussionmentioning
confidence: 99%